Completing the picture on student performances in OSCEs: A mixed-methods study on integration of a standardized patient rating. Issue 1 (January 2021) - Lörwald, Andrea; Lahner, Felicitas-Maria; Stricker, Daniel; Huwendiek, Sören
Highlights: Standardized patients (SPs) assessed physician–patient relationship and communication. Physician and SP assessments in OSCEs differ for student communicative competency. Physician–SP relationship is related to perception of student communication. Including SP rating in OSCEs would lead to increased student failure rates. Including SP rating in OSCEs would provide increased measurement precision of OSCEs. Abstract: Objective: Good physician communication skills increase patient satisfaction and improve healing processes. Although physicians and patients appear to value communicative competencies differently, students are often evaluated solely by physicians. This study examines whether additional assessment of students by 'standardized patients' (SPs) is useful. Methods: During their Objective Structured Clinical Examination (OSCE) 238 medical students were additionally rated by SPs at 9 stations according to two items that defined the 'physician–patient relationship' and 'communication'. SPs were informed that their assessment was for research purposes only, with no impact on the assessment of the students. SPs also had the opportunity to comment on their rating of the students. Results: The SPs rated the communicative competencies of students differently than physicians. The two parts of the SP rating are closely related. Inclusion of SP rating in the OSCE would provide higher measurement precision, with more students failing. SPs considered five factors relevant in their rating: 'human connection', 'information flow', 'professionalism', 'competence', and 'exam situation'. Conclusion: Our study suggests inclusion of SP rating as additional assessment of student communication skills. Practice Implications: Addition of SP rating in assessments is worthwhile, as it appears to complete the picture of the student performance in their OSCEs.